2023
DOI: 10.3233/thc-236039
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology and experimental studies for deciphering the molecular targets and mechanisms of Chaihu Shugan powder in the treatment of functional dyspepsia

Abstract: BACKGROUND: Chaihu Shugan powder (CSP) is a prevalent prescription product used in the treatment functional dyspepsia (FD) in China. However, the underlying pharmacological mechanisms involved in the treatment of FD remain unclear. OBJECTIVE: To explore the key components of CSP and their molecular targets and mechanisms in the treatment of FD. METHODS: Active compounds for CSP were identified from the TCMSP and SymMap databases, and the relevant targets were predicted. FD-related targets were obtained from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It is mainly used for the treatment of chronic hepatitis, chronic gastritis, intercostal neuralgia, and liver qi depression. 124 Further studies indicated that the formula increased miR-155 expression, inhibiting the TLR4 /NF-κB signaling pathway, activated the NLRP3 inflammasome, and reduced TLR4, NF-κB, NLRP3, Caspase-1, ASC and IL - 1β expression. 125 Amusingly, researchers have also presented new insights into TCM-ncRNA-pyroptosis in liver diseases.…”
Section: Traditional Chinese Medicine and Its Active Ingredients Infl...mentioning
confidence: 99%
“…It is mainly used for the treatment of chronic hepatitis, chronic gastritis, intercostal neuralgia, and liver qi depression. 124 Further studies indicated that the formula increased miR-155 expression, inhibiting the TLR4 /NF-κB signaling pathway, activated the NLRP3 inflammasome, and reduced TLR4, NF-κB, NLRP3, Caspase-1, ASC and IL - 1β expression. 125 Amusingly, researchers have also presented new insights into TCM-ncRNA-pyroptosis in liver diseases.…”
Section: Traditional Chinese Medicine and Its Active Ingredients Infl...mentioning
confidence: 99%